Health effects of exposure to indoor formaldehyde in civil buildings: A systematic review and meta-analysis on the literature in the past 40 years. (1st April 2023) - Liu, Ningrui; Fang, Lin; Liu, Wei; Kan, Haidong; Zhao, Zhuohui; Deng, Furong; Huang, Chen; Zhao, Bin; Zeng, Xiangang; Sun, Yuexia; Qian, Hua; Mo, Jinhan; et al.
Abstract: Exposure to indoor formaldehyde has been reported to be relevant to several adverse health effects, especially in occupational exposure scenarios. In this study, a systematic review and meta-analysis has been conducted for epidemiological studies published between January 1980 and December 2017 in order to summarize available evidence and to obtain concentration-response (C-R) relationships between different health outcomes and formaldehyde exposure in residences, offices or schools. We searched four databases to identify the related studies. Finally, we selected 31 studies through the systematic review, and included 23 studies in the meta-analysis. The results show that the pooled odds ratios (ORs) for asthma in children were 1.27 (95% CI: 1.20–1.35) in eastern countries and 1.03 (95% CI: 1.02–1.04) in western countries per 10 μg/m 3 increase in formaldehyde concentration. For asthma in adults, the pooled OR was 1.09 (95% CI: 1.03–1.15) per 10 μg/m 3 increase of formaldehyde concentration. We did not obtain significant associations of formaldehyde exposure with dermatitis or rhinitis. Our findings provide robust evidences for C-R relationships of formaldehyde exposure in civil buildings for different adverse health outcomes. The obtained C-R relationships can be helpful to estimate the attributable disease burden of indoor formaldehyde exposure. Graphical abstract: Image 1